2004
DOI: 10.1002/num.20040
|View full text |Cite
|
Sign up to set email alerts
|

A mesh‐free approach to solving the axisymmetric Poisson's equation

Abstract: In this article, we extend previous work of Karageorghis and Fairweather (Int J Numer Methods Engng 44 (199), 1653–1669) on the method of fundamental solutions (MFS) for solving Laplace's equation in axisymmetric geometry to the case of Poisson's equation. When the boundary condition and source term are axisymmetric, the problem reduces to solving the Poisson's equation in cylindrical coordinates in the two‐dimensional (r, z) region of the original three‐dimensional domain S. Hence, the original boundary value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 11 publications
0
13
0
1
Order By: Relevance
“…The condition of isolation is not needed if the exterior mass is distributed spheroidally and rotating. The complexity of (17) is consistent with the axisymmetric version of Poisson's equation being difficult to solve [63] even under constant density.…”
Section: Derivation Of Poisson's Equation From the Theorem Of Gaussmentioning
confidence: 54%
“…The condition of isolation is not needed if the exterior mass is distributed spheroidally and rotating. The complexity of (17) is consistent with the axisymmetric version of Poisson's equation being difficult to solve [63] even under constant density.…”
Section: Derivation Of Poisson's Equation From the Theorem Of Gaussmentioning
confidence: 54%
“…A comprehensive study of the analytical particular solutions of Chebyshev polynomials for polyharmonic and poly-Helmholtz operators was given by Tsai [22]. For axisymmetric operators, Chen et al [23] and Muleshkov et al [24] found the analytical particular solutions of Chebyshev polynomials for the Laplacian and Helmholtz operators, respectively. In this paper, we extend their work to axisymmetric polyharmonic and poly-Helmholtz operators using Chebyshev polynomials.…”
Section: Article In Pressmentioning
confidence: 99%
“…We refer readers for more details to the review papers by Fairweather and Karageorghis [1] and Golberg and Chen [2]. The MFS has also been applied for the solution of the axisymmetric Laplace equation [23,30] and the axisymmetric Helmholtz equation [31]. To obtain the axisymmetric fundamental solutions, we can integrate the non-axisymmetric fundamental solutions analytically over a ring.…”
Section: Article In Pressmentioning
confidence: 99%
“…the convergent rate of this approach is slow. Golberg et al [13] and Chen et al [12] approximate the source term f by applying Chebyshev interpolation so that the approximate particular solution can be evaluated. Despite the property of spectral convergence of Chebyshev interpolation, term by term monomial expansion is required so that the closed form particular solution for some particular differential operators can be derived.…”
Section: Introductionmentioning
confidence: 99%
“…(ii) The closed form approximate particular solution is difficult to derive for general differential operator L. As a result, polynomial and trigonometric approximation [12][13][14][15][16] have been re-examined to mitigate some of these difficulties. Recently, Li and Chen [14] employed the scheme of hyper-interpolation [17] for solving a series of elliptic equations and time-dependent problems.…”
Section: Introductionmentioning
confidence: 99%